Phytochemicals and In-Vitro Antioxidant Activities of Aloe Vera Gel - uddin, Md Nazim; roy, Subrata Chandra; mamun, Abdulla All; mitra, Kanika; haque, Md Zahurul; hossain, Mohammad Lokman (Journal of Bangladesh Academy of Sciences, 2020)
The phytochemicals (total phenolic, tannin, flavonoid, alkaloid, and saponin) contents in the Aloe vera gel derived from the leaf of Aloe vera (L.) Burm. f. (Synonym Aloe barbadensismiller) were extracted and their antioxidant capacity was studied by Ferric reducing antioxidant power assay (FRAP), by free radical-scavenging capability using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). Three different solvents with three different polarities CH3OH, CH3OH: HCl, CH3CH3OH: H2O were used at v/v ratio of 100, 98:2, 70:30, respectively. The acidified methanol solvent extracted the highest amounts of phytochemicals including total phenolic (4.64 mg gallic acid equivalent/g), tannin (3.84 mg tannic acid equivalent/g), alkaloid (662 mg piperine equivalent/g), and saponin (353 mg diosgenin equivalents/g) compared to the other two solvents. Similarly, in the extract with acidified methanol solvent, high level of total antioxidant activity (about 12 mg gallic acid equivalent/g) and scavenging effects expressed as 50% inhibition concentrations (IC50) for DPPH and ABTS assay were determined to be about 61 μg/mL and 371 μg/mL, respectively, which are higher than those with the other two solvents. The gel extract could be used as a potent antioxidant in medicine and food industries. Journal of Bangladesh Academy of Sciences, Vol. 44, No. 1, 33-41, 2020